Habitat heterogeneity facilitates coexistence of two syntopic species of Peromyscus in a temperate forest of Central México - De-la-Cruz, Ivan M.; Castro-Campillo, Alondra; Salame-Méndez, Arturo (THERYA, 2021)
An essential topic in ecology is to understand how the structure of the habitat and its changes in space and time (i. e., habitat heterogeneity) affect the frequency and interactions between cohabiting species. Here, we assessed the effect of the biotic and abiotic components that configure the microhabitat heterogeneity and its temporal shifts (dry and rainy seasons), on the frequency (total and by sex) of two congeneric species, Peromyscus difficilis and P. melanotis, that co-occurs in a temperate forest of Central Mexico. To address this, an experimental plot composed of 120 sampling stations was placed within a temperate forest in the National Park Desierto de los Leones, Mexico City. In each sampling station, we set Sherman traps to capture mice of two syntopic Peromyscus, and we also evaluated six variables related to the spatial heterogeneity of the habitat during two rainy seasons. Our results revealed differential effects of habitat heterogeneity on the frequency of each species. Moreover, habitat heterogeneity also had a different effect on male and female frequencies of each Peromyscus species. While P. difficilis was captured more frequently in sampling stations with high presence and coverage of logs in the soil, P. melanotis was regularly captured in sampling stations with high vegetation cover and plant species richness. Thus, it seems that the different requirements and habitat preferences of these two Peromyscus species facilitate their spatial and temporal coexistence in this mid-latitude temperate forest. In general, we provide evidence of the importance of studying the heterogeneity of the habitat to better understand the interactions between syntopic species, offering new insights into the spatial and temporal mechanisms that could determine its coexistence at local scale.